PERAN PASAR TANI TERHADAP PENINGKATAN PENDAPATAN ANGGOTA PASAR TANI DI KOTA YOGYAKARTA - Rahmatdi, Rahmatdi; Widiatmi, Susi; Maharani, Artita Devi (JURNAL ILMIAH AGRITAS, 2023)
This research aims to determine the effect of the role of the farmer's market in increasing the income of members of the farmer's market in the city of Yogyakarta. The research method used in this research is descriptive quantitative. The population and sample in this study were members of Pasar Tani in the city of Yogyakarta, amounting to 40 people. Data collection techniques used by this researcher are observation, questionnaires, and documentation. The data analysis technique in this reasearch used descriptive quantitative data analysis techniques. The results showed that there was an increase in the income of members of the farmer market in the city of Yogyakarta by 28.82%. This increase is based on a comparison of the income calculation of farmer market members from 2018 and 2019 which is Rp. 371,497,150.00. Based on the research analysis, it can be concluded that the existence of a farmer's market in the city of Yogyakata has a positive and significant effect on increasing the income of farmers' market members. Keywords : role, farmer market, increasing income